The 'pay now argue later' principle in South African Tax Law: its development, operation, comparison to South African civil debt enforcement and consistency with the constitutional right of access to courts - Elliott, Sarah (Department of Finance and Tax, 2017)
Section 164 of the Tax Administration Act 28 of 2011 (the TAA), previously contained in section 88 of the Income Tax Act 58 of 1962 (the Income Tax Act) and section 36 of the Value-Added Tax (VAT) Act 89 of 1991 (the VAT Act), provides that the payment of tax will not be automatically suspended until the resolution of a dispute regarding the liability for the said tax debt. This is known as the 'pay now argue later' principle. The objectives of this research were to analyse the development of the 'pay now argue later' principle in South African tax law, to provide an overview of the content and operation of section 164 of the TAA, to compare the principle and its purpose with civil debt enforcement procedures and, lastly, to test the principle against the Constitution of the Republic of South Africa, 1996 (the Constitution), specifically the right of access to courts. The underlying theme of this research is the recognition of taxpayers' rights in South Africa, specifically the interplay between the powers of the fiscus and the rights of taxpayers. In order to achieve the abovementioned objectives, this research examined the development of the 'pay now argue later' principle from its first appearance in section 88 of the Income Tax Act and section 36 of the VAT Act to its subsequent incorporation into the Tax Administration Bill 11 of 2011 and, ultimately, into section 164 of the TAA. It was concluded that the development of the 'pay now argue later' principle, from its first appearance in the Income Tax Act in 1962 and the VAT Act in 1993 until their repeal in 2011, was relatively minor save for in 2009, during which year there was a marked change in the structure of this principle with the inclusion of the so-called 'suspension rule'. This research provided a practical overview and understanding of the operation of the 'pay now argue later' principle in terms of section 164 of the TAA, specifically focusing on the suspension rule. This research further compared the 'pay now argue later' principle with civil debt enforcement procedures, specifically provisional sentence and summary judgment. It was concluded that the 'pay now argue later' principle is an exception to the ordinary rules governing civil debt enforcement proceedings. Lastly, this research placed the 'pay now argue later' principle under constitutional scrutiny, specifically whether its application infringes on the right of access to courts of taxpayers. It was found that the 'pay now argue later' principle infringes a taxpayer's right of access to courts, but this limitation is justified in terms of section 36 of the Constitution.